2019
DOI: 10.1111/1742-6723.13258
|View full text |Cite
|
Sign up to set email alerts
|

Our observations with cold calling: Patient anger and undesirable experiences

Abstract: Little is known about the effects of the ‘cold calling’ technique (telephone contact without prior warning) for patient follow up in ED research. Recently, we undertook a prospective, observational pain management study. Patients were cold called 48 h post‐discharge and surveyed regarding their pain management satisfaction. We made contact with 778 patients. Among these, we observed 12 cases of patient anger: mistaken identity, disbelief that the hospital was calling, frustration that test results and appointm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…1 Even when investigators have no established relationship with potentially eligible patients, they could invite them to participate in research, a recruitment approach borrowed from commercial settings also known as cold-contact. 2 Utilization of cold-contact as a recruitment tactic varies amongst academic medical centers. 3 Some institutions use an opt-in approach to cold-contact.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Even when investigators have no established relationship with potentially eligible patients, they could invite them to participate in research, a recruitment approach borrowed from commercial settings also known as cold-contact. 2 Utilization of cold-contact as a recruitment tactic varies amongst academic medical centers. 3 Some institutions use an opt-in approach to cold-contact.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, investigators have identified the potential for this type of patient engagement to enhance and expand recruitment strategies [1]. Even when investigators have no established relationship with potentially eligible patients, they could invite them to participate in research, a recruitment approach borrowed from commercial settings also known as cold contact [2]. Utilization of cold contact as a recruitment tactic varies amongst academic medical centers [3].…”
Section: Introductionmentioning
confidence: 99%